2021
DOI: 10.3390/jmp2040024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Features of Anti-CENP-B Autoantibodies

Abstract: Centromeric proteins are the foundation for assembling the kinetochore, a macromolecular complex that is essential for accurate chromosome segregation during mitosis. Anti-centromere antibodies (ACAs) are polyclonal autoantibodies targeting centromeric proteins (CENP-A, CENP-B, CENP-C), predominantly CENP-B, and are highly associated with rheumatologic disease (lcSSc/CREST syndrome). CENP-B autoantibodies have also been reported in cancer patients without symptoms of rheumatologic disease. The rise of oncoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…As shown in Figure 2, CENP‐B can be divided into 4 domains and encompasses two primary ACA epitopes. Between the DDE and dimerization domains are two acidic domains composing the mACA2 epitope of CENP‐B 7 . Our analysis indicates most of the abovementioned heptapeptide matches are located at the mACA2 epitope of CENP‐B.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As shown in Figure 2, CENP‐B can be divided into 4 domains and encompasses two primary ACA epitopes. Between the DDE and dimerization domains are two acidic domains composing the mACA2 epitope of CENP‐B 7 . Our analysis indicates most of the abovementioned heptapeptide matches are located at the mACA2 epitope of CENP‐B.…”
Section: Resultsmentioning
confidence: 71%
“…Between the DDE and dimerization domains are two acidic domains composing the mACA2 epitope of CENP-B. 7 Our analysis indicates most of the abovementioned heptapeptide matches are located at the mACA2 epitope of CENP-B. Besides, other heptapeptide matches have been found to locate at the DDE endonuclease domain or between the DNA binding and DDE domains.…”
Section: Heptapeptide Sharing Between Centromere Proteins and Human P...mentioning
confidence: 60%
See 1 more Smart Citation
“…Numerous studies have demonstrated the dysregulation of autoantibodies to intracellular components, such as centromeric proteins, which are the basis for the assembly of the kinetochore, a macromolecular complex essential for the precise segregation of chromosomes during mitosis. 1 Anticentromere antibodies (ACAs), polyclonal autoantibodies directed primarily to three of all the centromeric proteins (CENPA, CENPB and CENPC) 2,3 , are detected in patients with various autoimmune, rheumatologic and cancer diseases. 1 ACAs are considered diagnostic biomarkers in systemic sclerosis (SSc) and are mainly associated with the limited cutaneous subset (lSSc) of this disease which is also known as the CREST syndrome.…”
mentioning
confidence: 99%
“…1 Anticentromere antibodies (ACAs), polyclonal autoantibodies directed primarily to three of all the centromeric proteins (CENPA, CENPB and CENPC) 2,3 , are detected in patients with various autoimmune, rheumatologic and cancer diseases. 1 ACAs are considered diagnostic biomarkers in systemic sclerosis (SSc) and are mainly associated with the limited cutaneous subset (lSSc) of this disease which is also known as the CREST syndrome. Deregulation of ACAs has also been reported in systemic lupus erythematosus (SLE), primary biliary cholangitis (PBC), rheumatoid arthritis (RA), Sjogren Syndrome (SjS) and Raynaud's phenomenon.…”
mentioning
confidence: 99%